"LOVELY PAYABLE" AKUNTAN PEREMPUAN - Monica Citra Qurrota Aini; Krisno Septyan (Veteran Economics, Management, & Accounting Review, 2024)
This study aims to delve into the phenomenon of 'lovely payable' among female accountants. This research uses qualitative methods qualitative method with a case study approach, data collection techniques encompassed interviews, observations, and documentation. The participants in this research are a female auditor at PwC and a female financial staff at the BPJS office. The findings highlight that 'lovely payable' emphasizes the importance of time, particularly in providing brief yet meaningful quality time for children. Communication, especially through quality time, is considered crucial for maximizing the relationship between a career-oriented mother and her children. In deciding to be both an accountant and a mother, the research indicates that this choice is not solely about work pressures but also about creating harmony in the quality of life and meeting the emotional needs of the children.